Far-Side Audible Beaconing of Accessible Pedestrian Signals: Is It Confusing?. Issue 1 (January 2014) - Scott, Alan C.; Bentzen, Billie Louise; Barlow, Janet M.; Guth, David; Graham, Jennifer
Research has demonstrated that accessible pedestrian signals (APS) with push button–integrated speakers increase push-button use and increase the likelihood of starting to cross during the walk interval by pedestrians who are blind. However, consistently positive effects on locating the crosswalk or establishing or maintaining an accurate heading for crossing have not been found. Attempts have recently been made to configure APS to provide better audible information for these wayfinding tasks. A configuration that has been shown to improve heading accuracy provides audible tones from a speaker at the destination corner before the walk interval (to assist with establishing heading) and during the flashing "Don't Walk" interval (to assist with maintaining heading). Major concerns are that beaconing information may be ambiguous or misleading and result in dangerous crossing behavior at intersections where buildings create echoes of audible signal information and where beacons for multiple crosswalks might be active simultaneously. This study evaluated the effects of a beaconing APS system on pedestrian crossing behavior at an acoustically complex intersection and with multiple beacons sometimes concurrently active. Eighteen participants who were totally blind attempted a total of 216 crossings under three conditions. The results revealed no evidence that participants were distracted or were misled by concurrent beaconing information coming from a corner other than the target destination. Moreover, despite an acoustically complex environment, the beacon led to improved wayfinding Performance in some conditions and showed no evidence of having any deleterious effects.